Biotic and abiotic controls on nitrogen leaching losses into waterways during successive bovine urine application to soil. (1st July 2016) - Neilen, Amanda D.; Chen, Chengrong R.; Faggotter, Stephen J.; Ellison, Tanya L.; Burford, Michele A.
Abstract: Cattle waste products high in nitrogen (N) that enter waterways via rainfall runoff can contribute to aquatic ecosystem health deterioration. It is well established that N leaching from this source can be reduced by plant assimilation, e.g. pasture grass. Additionally, N leaching can be reduced when there is sufficient carbon (C) in the soil such as plant litterfall to stimulate microbial processes, i.e. denitrification, which off-gas N from the soil profile. However, the relative importance of these two processes is not well understood. A soil microcosm experiment was conducted to determine the role of biotic processes, pasture grass and microbial activity, and abiotic processes such as soil sorption, in reducing N leaching loss, during successive additions of bovine urine. Pasture grass was the most effective soil cover in reducing N leaching losses, which leached 70% less N compared to exposed soil. Successive application of urine to the soil resulted in N accumulation, after which there was a breaking point indicated by high N leaching losses. This is likely to be due to the low C:N ratio within the soil profiles treated with urine (molar ratio 8:1) compared to water treated soils (30:1). In this experiment we examined the role of C addition in reducing N losses and showed that the addition of glucose can temporarily reduce N leaching. Overall, our results demonstrated that plant uptake of N was a more important process in preventing N leaching than microbial processes. Highlights: Grass covered soil leached 30% of the added bovine urine N over a 60 d period. Plant use of N was more important for capturing N than microbial processes. Glucose C addition were found to enhance microbial activity, rather than biochar. Potential scope to reduced N leaching loss further though C amendments to pastures.